PENDIDIKAN KARAKTER MELALUI INTERNALISASI NILAI-NILAI AGAMA ISLAM PADA ANAK USIA DINI - Hani Hadiati Pujawardani (Media Nusantara, 2019)
Early childhood is called as the golden age of growth and development. Character education to the early child is an effort to build strong character and to create whole human being that can be done as early as possible in the era of globalization and industrial revolution 4.0. This research’s aim to find out the implementation of character education to the early child through internalization of Islamic values to form children with strong and good character. The character values: have believe and fear Allah Almighty, have a certain character, healthy, knowledgeable, skilled, creative, be autonomous, democratic, and to be responsible. This research use a qualitative approach with descriptive method, it means the research is aimed at describing and analyzing phenomena, screenings, and the implementation of character education in the early childhood. Data collected using observation, interview, and documentation study techniques. The results showed that: 1) the purpose of character education in early childhood has been refer to the goals of national education, 2) internalization strategy of Islamic religious values for the early childhood using the methods exemplary, habituation, take lessons from the story, demonstration and practice, motivation with reward, sosiodrama and field trips, 3) the evaluation of character education to the early childhood is to measurethe extent to which early childhood have a set of characters expected by usingassessment and observation instruments, 4) collaboration between parents andschools is well established and forms a partnership in the POMG organization.